Novel cochlear implant assessment tool: Comparative analysis of children and adults - Caldas, Fernanda Ferreira; Buzo, Byanka Cagnacci; Masiero, Bruno Sanches; Takeuti, Alice Andrade; Cardoso, Carolina Costa; Elias, Thais Gomes Abrahão; Bahmad, Fayez (Frontiers in Neurology, 2023)
Objectives To analyse the results of children and adults with cochlear implants (CIs) in pure tone audiometry (PTA) and speech perception tests. Tests were performed in two ways: using loudspeakers in the sound booth (SB) and with direct audio input (DAI) employing the Cochlear Latin America BOX (CLABOX). Methods Fifty individuals (33 adults and 17 children) participated in the study, including children aged between 8 and 13 years; of these, 15 users had bilateral CIs, 35 had unilateral CIs, and all had severe to profound bilateral sensorineural hearing loss. All participants were evaluated in the SB with loudspeakers and the CLABOX with DAI. The following evaluations were conducted: PTA, speech recognition tests with the hearing in noise test (HINT). Results The results for PTA and HINT conducted in SB and with CLABOX presented no significant difference between children and adults. Conclusion The CLABOX tool presents a new possible method to evaluate PTA and speech recognition tests in adults and children, with results comparable to the conventional evaluation in the SB.